THE SPIRIT OF SPORT: EXPLORING SPORTSMANSHIP AMONG PHYSICAL EDUCATION STUDENTS - Louie Galvez Giray (Acitya: Journal of Teaching and Education, 2021)
This research was conducted to explore the perception of physical education students in a Philippine school about sportsmanship. It particularly dealt with respect (1) for the opponent, (2) for rules and officials, and (3) for social conventions. This research used a qualitative descriptive method of research, with survey-questionnaire as the main data gathering tool. It was adapted from a valid and reliable instrument known as multidimensional sportspersonship orientations scale. In regard to respect for social conventions, participants perceived themselves as people who rarely congratulate the opponent, and infrequently shake hands with the opponent’s coach when they lose. Respect for the rules and the officials got good scores. Respect and concern for the opponent got low scores. They professed that they rarely do necessary actions when an opponent is unjustly penalized, hurt, or forgets his or her equipment. To achieve victory does not solely undermine character. It can be a good avenue to harness physical improvement and love for the sports. However, when the virtue of sportsmanship is discounted and forgotten, the result can be disadvantageous or even disastrous. Conclusions and recommendations were presented.